1995
DOI: 10.1136/jcp.48.6.582
|View full text |Cite
|
Sign up to set email alerts
|

Histological features of the thyroid gland in a patient with lithium induced thyrotoxicosis.

Abstract: Angiitis por hipersensibilidad y hepatitis granulomatosa inducida por glibenclamida: a proposito de un caso. Med Clin (Barc) 1980;75:306-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
21
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 11 publications
5
21
0
2
Order By: Relevance
“…Hyperthyroidism is rare in lithium-treated patients. In most cases, it occurs after many years of treatment (2,3,39). Consistent with the literature, among 84 patients, only 1 (1.2%) case of subclinical hyperthyroidism was found.…”
Section: Discussionsupporting
confidence: 77%
“…Hyperthyroidism is rare in lithium-treated patients. In most cases, it occurs after many years of treatment (2,3,39). Consistent with the literature, among 84 patients, only 1 (1.2%) case of subclinical hyperthyroidism was found.…”
Section: Discussionsupporting
confidence: 77%
“…Whilst psychiatrists prescribing lithium for bipolar affective disorder can expect the development of hypothyroidism in up to 30% of patients (5, 6), the emergence of thyrotoxicosis in relation to lithium treatment remains a paradoxical, rare and poorly explained phenomenon. Our literature search has yielded about 50 previously reported cases of lithium‐associated hyperthyroidism, some of these occurring on lithium withdrawal but none on dose reduction (3–16). Statistical analysis however has shown that long‐term lithium therapy is associated with an increased risk of thyrotoxicosis (4).…”
mentioning
confidence: 99%
“… an autoimmune thyroid disease triggered off by lithium (5–9, 16); disturbed iodine kinetics with escape phenomenon and ‘overflow’ of thyroid hormone after expansion of the intrathyroidal iodine pool (3, 4, 6, 12, 13); a Jod–Basedow‐like phenomenon (3); direct damage by lithium of thyroid follicular cells with subsequent release of thyroglobulin into the circulation (10, 14); coincidental Graves’ disease (16) or other coincidental hyperthyroidism. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that lithium may directly damage thyroid follicular cells, which is the cause of transient thyrotoxicosis in patients with lithium-induced painless thyroiditis 10) . Such follicular destruction has also been reported in amiodarone-induced thyrotoxicosis 11) .…”
Section: Discussionmentioning
confidence: 99%